Developmental Changes of Inhibitory Synaptic Currents in Cerebellar Granule Neurons: Role of GABA(A) Receptor α6 Subunit - Tia, Sutthichai (J Neurosci, 1996)
Eye opening and increased motor activity after the second postnatal week in rats imply an extensive development of motor control and coordination. We show a parallel developmental change in spontaneous IPSC (sIPSC) kinetics in cerebellar granule neurons. sIPSCs were studied by whole-cell recordings in cerebellar slices, prepared from 7–30 postnatal day old rats. Early in development, sIPSCs had slow decay kinetics whereas in older rats faster decaying sIPSCs were found in larger proportion. Currents elicited by 1 mmGABA pulses (GABACs) in nucleated patches excised from cerebellar granule neurons revealed that GABACs kinetics better approximate sIPSC decay in young but not in more developed rats. The expression of α6 subunit of GABA(A) receptors, unique in cerebellar granule neurons, has been shown to increase during development. Therefore, we took advantage of the recently reported selective inhibition of GABA(A) receptors by furosemide to characterize the relative contribution of α6 subunits to native receptors in inhibitory synapses of cerebellar granule neurons. Although furosemide inhibition of sIPSCs amplitude was highly variable among distinct granule cells, it increased during development. At the same time, furosemide failed to inhibit sIPSCs recorded from Purkinje neurons. From the comparison of furosemide inhibition and kinetics of sIPSCs with GABACs recorded from mammalian HEK293 cells transfected with combinations of α1 and α6 GABA(A) receptor subunits together with β2γ2 subunits, we propose that an increased α6 subunit contribution in the molecular assembly of postsynaptic receptors in cerebellar glomeruli is responsible for the developmental changes observed.